2001
DOI: 10.1016/s0002-9440(10)61773-7
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase-Receptor/Integrin Complexes Are Functionally Involved in Adhesion and Progression of Human Breast Cancer in Vivo

Abstract: Interactions between specific cell-surface molecules, which include the urokinase receptor (uPAR) and integrins, are crucial to processes of tumor invasion and metastasis. Here we demonstrate that uPAR and beta1-integrins may cluster at distinct sites at the cell surface of metastatic MDA-MB-231 breast cancer cells and form functional complexes. Attachment assays performed in the presence of a synthetic peptide (p25), which interferes with the formation of uPAR-integrin complexes, reveal that uPAR is able to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 48 publications
5
67
0
1
Order By: Relevance
“…Previously, we have shown loss of uPA/ uPAR-mediated Erk activation with downregulation of uPAR expression in colon cancer cells (Ahmed et al, 2003a). uPA/uPAR interaction with b1 integrin has been shown to activate Erk pathway (Ahmed et al, 2003a) and disruption of this interaction can result in loss of adhesion and tumour progression in nude mice (van der Pluijm et al, 2001). The uPAR -integrin interaction is crucial as many integrin receptors activate intracellular signal pathways to fully activate cell survival and proliferation pathways (Miyamoto et al, 1996).…”
Section: Discussionmentioning
confidence: 96%
“…Previously, we have shown loss of uPA/ uPAR-mediated Erk activation with downregulation of uPAR expression in colon cancer cells (Ahmed et al, 2003a). uPA/uPAR interaction with b1 integrin has been shown to activate Erk pathway (Ahmed et al, 2003a) and disruption of this interaction can result in loss of adhesion and tumour progression in nude mice (van der Pluijm et al, 2001). The uPAR -integrin interaction is crucial as many integrin receptors activate intracellular signal pathways to fully activate cell survival and proliferation pathways (Miyamoto et al, 1996).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, various subunits of integrin are abundantly expressed in melanomas and seem to play critical roles for melanoma metastasis. For instance, uPAR is known to associate with integrin b1 to promote tumor metastasis (16,31,33). In the current study, we have shown that d-GM3 promotes the association of uPAR and integrin a5b1, and the downstream activation of p38a is a key in melanoma invasion.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA were prepared using High Capacity cDNA Reverse Transcription kit (Applied Biosystems) with 2 mg of total RNA according to the manufacturer's protocol. The expression of GM3S, caveolin-1, integrin a3, a5, and b1 in cells was examined by PCR using primers with 200 ng cDNA per reaction as described previously (27,32,33). Glyceraldehyde 3-phosphate dehydrogenase (GAPDH) expression was detected as an internal control (33).…”
Section: Invasion Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…There is a close interplay between uPAR, integrins, vitronectin, and PAI-1 in regulating cell invasiveness. Multiple lines of evidence exist for association of uPAR with integrins to coordinate the effects of the two classes of receptors in mediating signaling and promoting cellular rearrangement and/or migration (57)(58)(59)(60)(61)(62)(63)(64)(65). This new information defining the relative location of binding sites for PAI-1 and the two receptors within the SMB domain will be invaluable for considering mechanisms by which these receptors and the ECM communicate in a reciprocal manner, ultimately with the goal of developing new antitumor and anti-thrombotic agents.…”
Section: Figmentioning
confidence: 99%